Heritage Education Memories of the Past in the Present Caribbean Social Studies Curriculum: A View from Teacher Practice - Con Aguilar, Eldris (Sidestone Press, 2020)
This book compiles the results of a doctoral research study that sought to gain insight into how indigenous heritage is represented in the school curriculum for social studies. To this end, the questions focused on studying the relationships that are formed between individuals and the past in the school context. Taking into account teachers' perspectives on subject content and pedagogical practices can contribute to gaining a better understanding of the role of education in safeguarding heritage. Heritage is continuously under threat from natural disasters; in recent years, the Caribbean region has suffered due to the increasing effects of climate change. But cultural and natural heritage are also threatened by human activity when members of a society forget their relationship with heritage and consequently stop caring about safeguarding it. A negligent attitude toward heritage can lead to acts of vandalism and destruction. Such a scenario poses special challenges to the education sector, which is ultimately seen as a source for positive change and development in society. This study, aimed at investigating the use of heritage education in the classroom, treats this subject in the form of analyses of three country case studies: the Dominican Republic, Dominica and Saint Kitts and Nevis. Along these lines, results were drawn from an informed analysis of educational policies concerning cultural heritage as well as accounts of teachers' perspectives on subject content and pedagogical practices. This study sought to shed light on the pedagogical practices used by teachers in the context of the three countries that formed this research. This research ultimately seeks to contribute to the fields of heritage education, teacher education and Caribbean studies by understanding the role of teacher knowledge and practices in safeguarding heritage-in this particular investigation, with a focus on the indigenous heritage of the Caribbean.